(untitled) (Revista Contexto & Saúde, 2024)
Objective: To evaluate the burden of family caregivers of cancer patients undergoing chemotherapy and to associate the burden of the caregiver with the sociodemographic, socioeconomic and clinical characteristics. Methods: Analytical study, conducted with 134 family caregivers. Caregivers over 18 years of age and whose patients were more than 12 months in treatment were included. Sociodemographic and clinical data were investigated and the Zarit Burden Interview Scale was used. For analysis, the mean and standard deviation were used, and the burden of work used Mann Whitney and Kruskall Wallis tests. Results: The survey involved 134 caregivers, mostly family members, female, between 30 and 39 years old, married, children of patients, with full elementary school, no formal employment, average income of 1 to 2 minimum wages, the time spent for care 1 to 3 months. The burden was evaluated in absent (44.8%), mild and moderate (41.8%), moderate to severe (12.7%) and intense (0.7%). Conclusion: Some family caregivers presented burden, mild to moderate, moderate to severe and intense. Gender, degree of kinship, absence from work activities, health problem, use of medications and time of illness were associated with the burden. The support and distribution of tasks among family members were fundamental to reduce the level of burden.